2015
DOI: 10.3892/ol.2015.4001
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-126 inhibits the migration and invasion of endometrial cancer cells by targeting insulin receptor substrate 1

Abstract: Abstract. MicroRNAs (miRs) have been demonstrated to serve important roles in the development and progression of human cancer, primarily through the direct targeting of oncogenes or tumor suppressors. It has been previously suggested that miR-126 may be associated with endometrial cancer (EC). However, the exact role of miR-126 in the migration and invasion of EC cells has not yet been studied. The present study demonstrated that the expression of miR-126 was significantly decreased in EC tissues when compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…Wang et al showed that IRS1 expression was significantly boosted in both breast cancer cell lines and tissues, and overexpression of IRS1 could reverse miR‐195‐mediated repression of tumour cell proliferation; moreover, miR‐195 inhibited tumour angiogenesis via IRS1. Zhao et al indicated that miR‐126 inhibited endometrial cancer cell migration and invasion through directly targeting IRS1. In addition, it has been reported that downregulation of IRS1 could inhibit the activation of AKT signalling pathway, which is implicated in tumorigenesis as well as development of osteosarcoma .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al showed that IRS1 expression was significantly boosted in both breast cancer cell lines and tissues, and overexpression of IRS1 could reverse miR‐195‐mediated repression of tumour cell proliferation; moreover, miR‐195 inhibited tumour angiogenesis via IRS1. Zhao et al indicated that miR‐126 inhibited endometrial cancer cell migration and invasion through directly targeting IRS1. In addition, it has been reported that downregulation of IRS1 could inhibit the activation of AKT signalling pathway, which is implicated in tumorigenesis as well as development of osteosarcoma .…”
Section: Discussionmentioning
confidence: 99%
“…For example, miRNA-505 functions as a tumor suppressor in endometrial cancer by targeting transforming growth factor (TGF)-α, whereas, miR-126 inhibits the migration and invasion of endometrial cancer cells by targeting insulin receptor substrate 1. In addition, miR-490-3P may act as a suppressor in the tumorigenesis and progression of endometrial cancer by targeting TGF-α (16,20,21). However, current understanding of the aberrant expression and potential roles of miRNAs remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs belongs to a class of non-coding small RNAs that comprise 18-23 nucleotides (Reddy, 2015). Previous studies have indicated that many miRNAs play an important role in carcinogenesis by regulating the expression of oncogenes and tumor suppressors (Zhang et al, 2015c;Zhao et al, 2016). Polymorphisms in miRNAs can alter the expression of proteins, thereby changing their function Song et al, 2016).…”
Section: Introductionmentioning
confidence: 99%